MORFOLOGIA E GÊNESE DE SOLOS PROVENIENTES DE ARENITOS DA FORMAÇÃO AQUIDAUANA - SOUSA, Maria Teresa Alves de; SCHIAVO, Jolimar Antonio; ARAÚJO, Karolline Almeida de; OLIVEIRA, Naelmo de Souza (ANAIS DO ENIC, 2025)
-